PENGARUH CAMPURAN COCOPEAT DAN ROCK PHOSPHATE TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS PADI GOGO (Oryza sativa L.) PADA MEDIUM ULTISOL - Rahmi Yulia; Nelvia Nelvia; Erlida Ariani (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2018)
The research aims to study the effect of mixture of cocopeat and rock phosphate on growth and yield of three varieties of upland rice in Ultisols medium. The research was conducted at the Green House of the Faculty of Agriculture, University of Riau, Pekanbaru from March to August 2017. The research used Split Plot Design. The main plot were upland rice consist of three varieties (Situ Bagendit, Situ Patenggang and Inpago 8). The subplots were mixture of cocopeat 10 t ha-1 with rock phosphate (RP) doses 0, 30, 45, and 60 P2O5 kg ha-1. The parameters observed were plant height, number of maximum tillers and productive tillers, panicle length, flowering age, number of grain panicle-1, weight of dry milled grain and weight of 1000 grain. The results showed that the application of mixture of cocopeat doses 10 t ha-1 and RP doses 30 – 60 P2O5 kg ha-1 have effect to plant height, panicle length, and weight 1000 grain for Situ Bagendit, Situ Patenggang and Inpago 8 compare to without RP, but tended increase number of maximum and productive tillers and decrease flowering age. The application cocopeat doses 10 t ha-1 and RP doses 30 P2O5 kg ha-1 increased number of filled grain panicle-1 and weight of dry milled grain on three varieties, weight of dry milled grain Situ Patenggang > Inpago 8 > Situ Bagendit on each doses of RP and have number of productive tillers of these varieties 1,5 – 2 is greater than its descriptions.Keywords : rock phosphate, ultisol, upland rice